Natural variation of AcEGY3 mediates chloroplastic ROS homeostasis to confer kiwifruit thermotolerance - Chengcheng Ling; Jun Yang; Jiale Xu; Wei Tang; Yunyan Liu; Yingzhen Wang; Pengwei Li; Yan He; Zhiyin Ouyang; Shuqi Chen; Fei Xing; Xinxin Wang; et al. (Nature Communications)
Abstract The genus of Actinidia consists of the popular kiwifruits consuming worldwide. Most kiwifruit species are naturally distributed in warm and moist environments. So, they are vulnerable to high levels of heat stress. Till now, genetic basis of kiwifruit thermotolerance has remained largely unexplored. Here, we uncover a natural variation responsible for thermotolerance in kiwifruit species. We reveal that thermotolerant kiwifruit species have increased expression of AcEGY3, a gene encoding a chloroplast-localized protein, which can promote expression of nuclear thermotolerance genes via H2O2-dependent retrograde signaling. We show that natural variation in the promoter of AcEGY3 constitute a binding site for the heat stress-inducible transcription factor AcGATA1. The increased expression of AcEGY3 is regulated by AcGATA1 and its possible interaction with another transcription factor AcHSFA2-2. This natural variation is absent from the thermosensitive kiwifruit species. Collectively, our results reveal genetic basis of kiwifruit thermotolerance and set the foundation for breeding thermotolerant kiwifruits cultivars.